Case Report: Cognitive Behavioral Therapy of A Patient With Pathological Gambling - S. Olga Guriz; Aslý Ekinci; M. Hakan Türkçapar (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Pathological gambling is a mental disorder characterized by continuous and repetitive gambling behavior and it might cause significant losses in social, professional and family life. There may also be some personal and social results of it such as suicide attempts, loss of job, marital problems, and troubles in family life, legal difficulties and criminal behavior. Co-occurring mental disorders might influence treatment outcomes of pathological gambling behavior. There are some reports suggesting that especially higher depression levels may increase the likelihood of gambling behavior and it has also been stressed that identification and early treatment of co-occurring depression in treatment process should improve the results and reduce relapse rates. There is not an standardized treatment modality for the treatment of the disorder. It is known that in the treatment of this condition, which results in personal and social failure, psychological intervention may have positive results both in the short and long term. As pathological gambling is not a homogenous disorder, individual planning is essential for the evaluation and therapy. Rational Emotive Behavior Therapy seems to be efficient in the treatment of pathological gambling especially in coping with emotional problems and feeling of discomfort through making up a holistic cognitive, emotional, and behavioral model. In this report, the effectiveness of Rational Emotive Behavior Therapy that accompanied a drug therapy is discussed in a case of a pathological gambling with comorbid depression. [JCBPR 2012; 1(2.000): 105-112]